Fear and trembling Repetition - Kierkegaard, Søren, 1813-1855 (Princeton University Press, 1983)
"Presented here in a new translation, with a historical introduction by the translators, Fear and Trembling and Repetition are the most poetic and personal of Søren Kierkegaard's pseudonymous writings. Published in 1843 and written under the names Johannes de Silentio and Constantine Constantius, respectively, the books demonstrate Kierkegaard's transmutation of the personal into the lyrically religious."--Publisher's website
Translation of: Frygt og bæven and of Gjentagelsen.
Keywords: Christianity -- Philosophy.; Sin.; Repetition (Philosophy); Christianisme -- Philosophie.; Péché.; Répétition (Philosophie); RELIGION -- Christianity -- General.; BODY, MIND & SPIRIT -- Gaia & Earth Energies.; Christianity -- Philosophy; Sin; Christelijke ethiek.; Christian philosophy.; Christian philosophy -- 19th century.; Christian ethics -- History -- 19th century.